2015
DOI: 10.1152/ajpcell.00402.2014
|View full text |Cite
|
Sign up to set email alerts
|

Secreted protein acidic and rich in cysteine facilitates age-related cardiac inflammation and macrophage M1 polarization

Abstract: Toba H, de Castro Brás LE, Baicu CF, Zile MR, Lindsey ML, Bradshaw AD. Secreted protein acidic and rich in cysteine facilitates age-related cardiac inflammation and macrophage M1 polarization. Am J Physiol Cell Physiol 308: C972-C982, 2015. First published April 15, 2015; doi:10.1152/ajpcell.00402.2014.-To investigate the role of secreted protein acidic and rich in cysteine (SPARC) in age-related cardiac inflammation, we studied six groups of mice: young (3-5 mo old), middle-aged (10 -12 mo old), and old (18 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 59 publications
4
40
0
Order By: Relevance
“…Indeed, the analysis of fibroblasts derived from aged MCP-1KO and aged B6J hearts demonstrated a 3 fold increased IL-6 mRNA expression (measured by qPCR [8]) in fibroblasts derived from the aged MCP-1KO heart, and although this difference did not reach statistical significance (2.95 ± 1.05 vs 1.00 ± 0.39, P=0.16), it suggests a potential mechanism by which aged MCP-1KO hearts still have a pro-inflammatory environment and partially develop myeloid-dependent fibrosis. An increased macrophage infiltration in the aged B6J mouse heart has been described by others [31, 48], and in these studies the ratio of M1 (classically activated pro-inflammatory macrophage) to M2 alternatively activated macrophage was increased. We have found that both M1 (data not published) and M2a macrophages had an increased presence in the aging heart when compared with young controls.…”
Section: Discussionsupporting
confidence: 70%
“…Indeed, the analysis of fibroblasts derived from aged MCP-1KO and aged B6J hearts demonstrated a 3 fold increased IL-6 mRNA expression (measured by qPCR [8]) in fibroblasts derived from the aged MCP-1KO heart, and although this difference did not reach statistical significance (2.95 ± 1.05 vs 1.00 ± 0.39, P=0.16), it suggests a potential mechanism by which aged MCP-1KO hearts still have a pro-inflammatory environment and partially develop myeloid-dependent fibrosis. An increased macrophage infiltration in the aged B6J mouse heart has been described by others [31, 48], and in these studies the ratio of M1 (classically activated pro-inflammatory macrophage) to M2 alternatively activated macrophage was increased. We have found that both M1 (data not published) and M2a macrophages had an increased presence in the aging heart when compared with young controls.…”
Section: Discussionsupporting
confidence: 70%
“…These changes are all blunted by SPARC deletion (Bradshaw et al 2010). Aging SPARC null mice (18–29 month old) also have decreased collagen type III and IV expression and macrophage infiltration compared to aging wild type control mice (de Castro Bras et al 2014; Toba et al 2015). The decrease in collagen III may result in an increased collagen I to collagen III ratio, which would also explain the increase in myocardial diastolic stiffness.…”
Section: Aging Effects On Cardiac Structure and Functionmentioning
confidence: 99%
“…Secreted protein acidic and rich in cysteine (SPARC) belongs to the matricellular protein family, and SPARC is involved in cross-linked collagen fibril formation (Bradshaw 2009). SPARC is predominantly expressed in cardiac fibroblasts, although cardiomyocytes, endothelial cells, and macrophages also exhibit low SPARC expression (Toba et al 2015). SPARC increases in the LV of 18 to 29 month old mice and has been linked to age-related increases in myocardial diastolic stiffness as well as fibrillar and insoluble collagen content.…”
Section: Aging Effects On Cardiac Structure and Functionmentioning
confidence: 99%
See 2 more Smart Citations